UNIVERSITASISASI STAIN MALANG: Analisis Kebijakan Publik Perubahan Kelembagaan Dalam Perspektif Filsafat Nilai - Esha, Muhammad In’am (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
This paper examines to study institutional change of the State Islamic University (SIU), Malang. This study gets some summaries: First, that institutional change of SIU indicates that social sphere of higher education coloured with struggle for implementation of Islamic universality in education field. Struggle in social sphere of higher education cannot be discharged from spirit of Islam people to make a